International expert consensus on the surgical anatomic classification of radical hysterectomies - Querleu, Denis; Cibula, David; Abu-Rustum, Nadeem R; Fanfani, Francesco; Fagotti, Anna; Pedone Anchora, Luigi; Ianieri, Manuel Maria; Chiantera, Vito; Bizzarri, Nicolò; Scambia, Giovanni (American journal of obstetrics and gynecology, 2024)
BACKGROUND: The anatomic descriptions and extents of radical hysterectomy often vary across the literature and operative reports worldwide. The same nomenclature is often used to describe varying procedures, and different nomenclature is often used to describe the same procedure despite the availability of guideline and classification systems. This makes it difficult to interpret retrospective surgical reports, analyze surgical databases, understand technique descriptions, and interpret the findings of surgical studies. OBJECTIVE: In collaboration with international experts in gynecologic oncology, the purpose of this study was to establish a consensus in defining and interpreting the 2017 updated Querleu-Morrow classification of radical hysterectomies. STUDY DESIGN: The anatomic templates of type A, B, and C radical hysterectomy were documented through a set of 13 images taken at the time of cadaver dissection. An online survey related to radical hysterectomy nomenclature and definitions or descriptions of the associated procedures was circulated among international experts in radical hysterectomy. A 3-step modified Delphi method was used to establish consensus. Image legends were amended according to the experts' responses and then redistributed as part of a second round of the survey. Consensus was defined by a yes response to a question concerning a specific image. Anyone who responded no to a question was welcome to comment and provide justification. A final set of images and legends were compiled to anatomically illustrate and define or describe a lateral, ventral, and dorsal excision of the tissues surrounding the cervix. RESULTS: In total, there were 13 questions to review, and 29 experts completed the whole process. Final consensus exceeded 90% for all questions except 1 (86%). Questions with relatively lower consensus rates concerned the definitions of types A and B2 radical hysterectomy, which were the main innovations of the 2017 updated version of the 2008 Querleu-Morrow classification. Questions with the highest consensus rates concerned the definitions of types B1 and C, which are the most frequently performed radical hysterectomies. CONCLUSION: The 2017 version of the Querleu-Morrow classification proved to be a robust tool for defining and describing the extent of radical hysterectomies with a high level of consensus among international experts in gynecologic oncology. Knowledge and implementation of the exact definitions of hysterectomy radicality are imperative in clinical practice and clinical research.
Keywords: classification; Female; ženské pohlaví; cervix uteri; lidé; Genital Neoplasms, Female; Querleu-Morrow; konsensus; Consensus; gynecologic oncology; retrospektivní studie; cervical cancer; hysterektomie; radical hysterectomy; nádory ženských pohlavních orgánů; Cervix Uteri; Retrospective Studies; Hysterectomy; Humans